2023
DOI: 10.1111/eci.13995
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of fornix in Alzheimer's disease: From basic research to clinical practice

Abstract: Alzheimer's disease (AD) is one of the most common progressive neurodegenerative diseases associated with the degradation of memory and cognitive ability. Current pharmacotherapies show little therapeutic effect in AD treatment and still cannot prevent the pathological progression of AD. Deep brain stimulation (DBS) has shown to enhance memory in morbid obese, epilepsy and traumatic brain injury patients, and cognition in Parkinson's disease (PD) patients deteriorates during DBS off. Some relevant animal studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Deep brain stimulation (DBS) has emerged as a potential method for improving cognitive function in AD through the modulation of neural circuits [ 291 ]. Compared to non-invasive neural modulation strategies, invasive DBS through implanted electrodes targets specific brain areas and provides real-time EEG-neurofeedback, resulting in better treatment effects [ 292 ]. Chronic fornix DBS treatment significantly reduced amyloid deposition in the hippocampus and cortex, decreased activation of astrocytes and microglia, and promoted neurogenesis [ 293 ].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep brain stimulation (DBS) has emerged as a potential method for improving cognitive function in AD through the modulation of neural circuits [ 291 ]. Compared to non-invasive neural modulation strategies, invasive DBS through implanted electrodes targets specific brain areas and provides real-time EEG-neurofeedback, resulting in better treatment effects [ 292 ]. Chronic fornix DBS treatment significantly reduced amyloid deposition in the hippocampus and cortex, decreased activation of astrocytes and microglia, and promoted neurogenesis [ 293 ].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
“…Interestingly, the rats treated with DBS showed a decrease in the number of abnormally activated astrocytes and morphological changes, indicating that DBS contributes to restoring the balance of the nervous system [ 293 ]. Clinical trials also found that DBS targeting the fornix helps to regulate cognitive ability and stabilize or attenuate memory impairment in mild AD patients [ 292 , 293 ]. Unfortunately, current DBS therapy targeting the fornix for AD only improves episodic memory in a subset of patients [ 294 ].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
“…DBS, specifically the fornix, is being investigated as a treatment for patients with mild AD. Results from randomized clinical trials have demonstrated an improvement in cognitive function among some patients and no benefit in others [ 209 ]. The fornix, a part of the Papez circuit, is the principal inflow and outflow tract of the hippocampus and middle temporal lobe.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%